Academic Hardiness pada Mahasiswa Aktivis dan Mahasiswa yang Bekerja. - Yosephin Priskila Febrianti; Fathul Lubabin Nuqul; Husnul Khotimah (Psyche 165 Journal, 2020)
The purpose of this study is to determine whether or not the differences in academic hardiness levels seen from college student's activity while working and student who actively participate in an organization. The approach of this research is quantitative by using the T-test analysis technique, while sampling uses the purposive sampling technique. The subjects in this study were students who studying while working and actively participate in an organization in a total of 120 people. Measuring tools to collect data using a scale of academic hardiness. Scale academic hardiness consists of 45 items (with reliability = 0.898). Based on the data analysis performed, the value of t count <t table is -1.973 <1.979 with p = 0.051 (p <0.05). These results indicate that there are no significant differences in academic hardiness levels in working student and student who actively participate in an organization. Then the hypothesis in this study was rejected.